An indoor air filtration study in homes of elderly: cardiovascular and respiratory effects of exposure to particulate matter - Karottki, Dorina Gabriela (BioMed Central, 2013)
BACKGROUND: Exposure to particulate air pollution increases respiratory and cardiovascular morbidity and mortality, especially in elderly, possibly through inflammation and vascular dysfunction. METHODS: We examined potential beneficial effects of indoor air filtration in the homes of elderly, including people taking vasoactive drugs. Forty-eight nonsmoking subjects (51 to 81 years) in 27 homes were included in this randomized, double-blind, crossover intervention study with consecutive two-week periods with or without the inclusion of a high-efficiency particle air filter in re-circulating custom built units in their living room and bedroom. We measured blood pressure, microvascular and lung function and collected blood samples for hematological, inflammation, monocyte surface and lung cell damage markers before and at day 2, 7 and 14 during each exposure scenario. RESULTS: The particle filters reduced the median concentration of PM(2.5) from approximately 8 to 4 μg/m(3) and the particle number concentration from 7669 to 5352 particles/cm(3). No statistically significant effects of filtration as category were observed on microvascular and lung function or the biomarkers of systemic inflammation among all subjects, or in the subgroups taking (n = 11) or not taking vasoactive drugs (n = 37). However, the filtration efficacy was variable and microvascular function was within 2 days significantly increased with the actual PM(2.5) decrease in the bedroom, especially among 25 subjects not taking any drugs. CONCLUSION: Substantial exposure contrasts in the bedroom and no confounding by drugs appear required for improved microvascular function by air filtration, whereas no other beneficial effect was found in this elderly population.